2016
DOI: 10.1038/srep31125
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of new RNA polymerase III and RNA polymerase II transcriptional promoters in the Bovine Leukemia Virus genome

Abstract: Bovine leukemia virus latency is a viral strategy used to escape from the host immune system and contribute to tumor development. However, a highly expressed BLV micro-RNA cluster has been reported, suggesting that the BLV silencing is not complete. Here, we demonstrate the in vivo recruitment of RNA polymerase III to the BLV miRNA cluster both in BLV-latently infected cell lines and in ovine BLV-infected primary cells, through a canonical type 2 RNAPIII promoter. Moreover, by RPC6-knockdown, we showed a direc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 69 publications
0
9
0
2
Order By: Relevance
“…Viral miRNAs are strongly expressed in preleukemic and malignant cells, and may have roles in tumor onset and progression [ 39 , 40 ] through their effects on proviral load and consequently viral replication in the natural host [ 41 ]. Besides, Van Driessche et al revealed the recruitment of positive epigenetic marks on BLV miRNA cluster, inducing strong antisense promoter activity [ 42 ]. They also identified cis -acting elements of an RNAPII-dependent promoter [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral miRNAs are strongly expressed in preleukemic and malignant cells, and may have roles in tumor onset and progression [ 39 , 40 ] through their effects on proviral load and consequently viral replication in the natural host [ 41 ]. Besides, Van Driessche et al revealed the recruitment of positive epigenetic marks on BLV miRNA cluster, inducing strong antisense promoter activity [ 42 ]. They also identified cis -acting elements of an RNAPII-dependent promoter [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Van Driessche et al revealed the recruitment of positive epigenetic marks on BLV miRNA cluster, inducing strong antisense promoter activity [ 42 ]. They also identified cis -acting elements of an RNAPII-dependent promoter [ 42 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers discovered that the BLV genome encodes 5 pre-microRNA (miRNA) hairpins that produce 10 mature miRNAs in a genomic region previously thought to be inactive ( 15 , 16 ). BLV miRNAs are atypical in several ways; virally encoded miRNAs are unusual in RNA viruses due to the potential for cleaving genomic RNA ( 15 ) and BLV miRNAs are transcribed by RNA polymerase III (RNAPIII), as opposed to the typical miRNA biosynthesis that utilizes RNAPII ( 15 18 ). Despite these unusual features, BLV miRNAs have been detected at levels equivalent to endogenous miRNAs in both bovine B-cell tumors ( 16 ) and in experimentally infected bovine calves ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to 5′ LTR directed transcription, antisense RNA synthesis initiating at the 3′ LTR is consistently identified in primary ATL cells and BLV tumors ( Usui et al, 2008 ; Saito et al, 2009 ; Durkin et al, 2016 ). In contrast to HTLV-1, BLV also abundantly transcribes a cluster of microRNAs from internal pol III promoters ( Kincaid et al, 2012 ; Rosewick et al, 2013 ; Van Driessche et al, 2016 ). These microRNAs are required for efficient viral replication and induction of pathogenesis ( Gillet et al, 2016 ).…”
Section: Experimental Evidence and Interpretationsmentioning
confidence: 99%